2019
DOI: 10.5194/bg-2019-322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drivers of diffusive lake CH<sub>4</sub> emissions on daily to multi-year time scales

Abstract: <p><strong>Abstract.</strong> Lakes and reservoirs are important emitters of climate forcing trace gases. Various environmental drivers of the flux, such as temperature and wind speed, have been identified, but their relative importance remains poorly understood. Here we use an extensive field dataset to disentangle physical and biogeochemical controls on the turbulence-driven diffusive flux of methane (CH<sub>4</sub>) on daily to multi-year… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 105 publications
(177 reference statements)
1
4
0
Order By: Relevance
“…As seen in other lake ecosystems, short-term variations in CH 4 flux can be driven by wind speed (26). This is in line with our data, which clearly showed that diel patterns of wind speed and CH 4 flux coincided with each other (SI Appendix, Fig.…”
supporting
confidence: 92%
“…As seen in other lake ecosystems, short-term variations in CH 4 flux can be driven by wind speed (26). This is in line with our data, which clearly showed that diel patterns of wind speed and CH 4 flux coincided with each other (SI Appendix, Fig.…”
supporting
confidence: 92%
“…In shallow waters, bubble mediated transport is the most efficient way of transferring methane to the atmosphere, bypassing methane oxidation in the oxic water column (McGinnis et al, 2006). Its temporal variability is a result of changes in local net methane production and accumulation in the sediment, and the episodic occurrence of triggers for bubble release (Varadharajan and Hemond 2012;Maecket al, 2014;Jansen et al, 2019). Whereas, spatial variability of ebullition in lakes and reservoirs results from variations of methane production rates in the sediment, which depend on sediment temperature (Wilkinson et al, 2015), sediment thickness (Maeck et al, 2013) and organic matter content (Grasset et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating data-and doing so across disciplines, beyond simple cataloging and indexing-becomes critically important as data analysis methods become increasingly sophisticated (Michener & Jones, 2012). As technological innovation allows, research is increasingly being performed across broader scales (e.g., from satellite data to processes at the micro and nanoscale) (Peters et al, 2008;Heffernan et al, 2014;Fei, Guo & Potter, 2016;Rose et al, 2017;Jansen et al, 2019a), and new and more diverse data are being generated. This has prompted international efforts to develop standards that make data more Findable, Accessible, Interoperable, and Reusable among different labs (FAIR principles) (Wilkinson et al, 2016;Brandizi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…daily and hourly weather summaries (including daily weather from 1913-present)Callaghan et al (2010),Jonasson, Johansson & Christensen (2012),, and numerous others Mire weather, soil temperature and moisture profiles, heat fluxes, and NDVI (continuous)Jansen et al (2019aJansen et al ( , 2019b andGarnello (2017) Lake water temperature profiles (continuous) XWik et al (2013) Gas fluxes:Total hydrocarbon, CH 4 , and CO 2 fluxes from autochambers XBäckstrand et al (2008aBäckstrand et al ( , 2008bBäckstrand et al ( , 2010, Jackowicz-Korczy nski et al(2010)and Holst et al (2010) δ 13 C values of CH 4 and CO 2 fluxes from autochambers McCalley et al (2014) Thaw pond bubble fluxes and associated temperatures X Burke et al (2019) Terrestrial subsurface geochemistry: CH 4 and CO 2 concentrations and δ 13 C values X McCalley et al (2014), Hodgkins et al (2015), Hodgkins (2016) and Perryman et al (2020) Dissolved species concentrations (DOC, TN, acetate and other VFAs, O 2 , PO 3− 4 , SO 2− 4 , NO − 3 , NH 3 , Mn, Fe, Ca, Mg) X Hodgkins (2016) and Perryman et al (2020) Peat water content X Hodgkins (2016) Peat bulk density Peat C and N concentrations, δ 13 C and δ 15 N, and C/N ratios X Hodgkins et al (2014) and Hodgkins (2016) Radiocarbon ages of peat and DIC X Hodgkins (2016) FT-ICR MS X (summarized indices) Tfaily et al (2012), Hodgkins et al (2014, 2016), Hodgkins (2016), Wilson et al (2017) and Wilson & Tfaily (2018) DOM optical properties (UV/Vis and EEMS) X (summarized indices) Hodgkins (2016) and Hodgkins et al (2016) Peat FTIR X (summarized indices) Hodgkins et al (2014, 2018) Results from peat incubations (CH 4 and CO 2 production and δ 13 C values) X (summarized indices) Hodgkins et al (2014, 2015), Hodgkins (2016), Wilson et al (2017, 2019), and Perryman et al (2020) Microbial and viral sequencing: 16S rRNA amplicons (~100) X McCalley et al (2014), Deng et al (2017), Mondav et al (2017), Martinez et al (2019) and Wilson et al (2019) Metagenomes (~375) X Mondav et al (2014), Singleton et al (2018), Woodcroft et al (2018) and Martinez et al (2019) Metatransciptomes (24) X Singleton et al (2018), Woodcroft et al (2018) and Martinez et al (2019) Metaproteomes (16) X Mondav et al (2014), Woodcroft et al (2018) and Martinez et al(2019)Viromes (65) XTrubl et al (2016Trubl et al ( , 2018Trubl et al ( , 2019 andRoux et al (2019) Viral population contigs mined from metagenomes XEmerson et al (2018) …”
mentioning
confidence: 99%